Pengaruh Komunikasi Pemasaran Sebagai Promosi untuk Usaha Kecil Menengah - Syahputri, Rima Rizki; M Nawawi, Zuhrinal (ManBiz: Journal of Management and Business, 2024)
To turn innovative ideas into viable businesses, an entrepreneur collects and brings together all the essential resources, such as money, people, business model, strategy and willingness to take risks. The marketing mix consists of four elements: product, price, location and promotion. Promotion as part of the marketing mix has a number of obstacles in terms of the effectiveness and efficiency of the marketing message to be conveyed. As a result, the concept of integrated marketing communication emerged, which integrates several marketing communication strategies to increase the effectiveness and efficiency of integrated marketing messages. An entrepreneur's ability to sell his brand will be aided by the knowledge, understanding and application of integrated marketing communications. The purpose of this study is to conduct a theoretical investigation of the relationship between entrepreneurship and integrated marketing communication as a marketing promotion approach. If done right, integrated marketing communications can help entrepreneurs introduce, form a positive impression, and retain clients for their companies.